Tuning the High‐Temperature Wetting Behavior of Metals toward Ultrafine Nanoparticles. (9th February 2018) - Zhou, Yubing; Natarajan, Bharath; Fan, Yanchen; Xie, Hua; Yang, Chunpeng; Xu, Shaomao; Yao, Yonggang; Jiang, Feng; Zhang, Qianfan; Gilman, Jeffrey W.; Hu, Liangbing
Abstract: The interaction between metal nanoparticles (NPs) and their substrate plays a critical role in determining the particle morphology, distribution, and properties. The pronounced impact of a thin oxide coating on the dispersion of metal NPs on a carbon substrate is presented. Al2 O3 ‐supported Pt NPs are compared to the direct synthesis of Pt NPs on bare carbon surfaces. Pt NPs with an average size of about 2 nm and a size distribution ranging between 0.5 nm and 4.0 nm are synthesized on the Al2 O3 coated carbon nanofiber, a significant improvement compared to those directly synthesized on a bare carbon surface. First‐principles modeling verifies the stronger adsorption of Pt clusters on Al2 O3 than on carbon, which attributes the formation of ultrafine Pt NPs. This strategy paves the way towards the rational design of NPs with enhanced dispersion and controlled particle size, which are promising in energy storage and electrocatalysis.